Benzene, Toluene, Xylene Levels and Subjective Complaints in Shoe Workshops - Taufik Ashar; Devi Nuraini Santi; Evi Naria (Jurnal Kesehatan Masyarakat, 2025)
The demand for shoes must be met by the worldwide shoe manufacturing business, but the inhalation dangers associated with its chemical processes—which use benzene, toluene, and xylene (BTX)—raise health issues for workers. Initial surveys showed that most shoe manufacturing workshops do not have adequate ventilation. Most workers often complain of symptoms such as coughing, shortness of breath, and headaches. This study examined the relationships between worker symptoms and chemical levels at shoe factories in Medan, Indonesia, in 2017. This was an observational cross-sectional study. The total population was 72 workers in shoe workshops in the small industrial center area in Medan city. The sample size in this study was 47 people in seven shoe workshops. BTX concentrations were measured in seven workshops. Statistical tests used in this study were chi-square test and Fisher’s exact test with a significance level of p<0.05. According to the findings, the most common symptoms among employees were coughing (40.4%), dizziness (55.3%), and eye discomfort (55.3% of respondents). The range values were 0.09 ppm to 2.83 ppm, 1.20 ppm to 178.98 ppm, and 0.11 ppm to 50 ppm for benzene, toluene, and xylene, respectively. The two compounds most commonly exposed to levels exceeding the ACGIH (American Conference of Governmental Industrial Hygienists) threshold level value were toluene (55.3%) and benzene (25.5%), according to ambient readings. Of the workshops that were inspected, only two (28.57%) had a functional ventilation system. Exposure to benzene exceeding the quality standard showed a significant association with dizziness (p = 0.003) and watery eyes (p = 0.003). Meanwhile, exposure to toluene exceeding the permissible limit was significantly associated with dyspnea (p = 0.005). Our research showed that over half of the workforce reported subjective complaints and that levels of benzene and toluene exceeded recommendations for occupational exposure.